PAINTING - THE ART OF COLOR (American Journal of Interdisciplinary Research and Development, 2022)
Painting is the art of painting. Painting is a type of fine art that reflects real life and influences the thoughts and feelings of the audience.A work of art on a surface, painted with paints (watercolor, tempera, watercolor, gouache, etc.) is called painting. The images in the painting are very bright and spectacular. Artists create their works with paintings and plastic tools. Although they use the possibilities of pencil and composition, one of the most effective means of painting is color.